1963
DOI: 10.1042/bj0880470
|View full text |Cite
|
Sign up to set email alerts
|

Dolichol: A Naturally-Occurring C100 Isoprenoid Alcohol

Abstract: region 190-210 mjA was determined by Dr C. von Planta (Hoffmann-La Roche and Co., Basle) using a vacuum grating spectrometer as described by Planta (1962). Infrared-absorption spectra were recorded by a Perkin-Elmer Infracord (model 137) spectrometer. The highresolution spectra were obtained by Dr C. H. Steele of the Thornton Research Laboratories, Shell, Ellesmere Port, Cheshire, with a Grubb-Parsons double-beam grating spectrometer (model GS 2). Samples were examined as films between NaCl plates whenever pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(72 citation statements)
references
References 12 publications
9
63
0
Order By: Relevance
“…All dolichols so far investigated are in the S-form, and probably only the trans-trans-polycis compound is present in biological membranes, again in contrast with ubiquinone, which is in the all-trans form [15][16][17].…”
Section: Structure Of Dolicholmentioning
confidence: 99%
See 1 more Smart Citation
“…All dolichols so far investigated are in the S-form, and probably only the trans-trans-polycis compound is present in biological membranes, again in contrast with ubiquinone, which is in the all-trans form [15][16][17].…”
Section: Structure Of Dolicholmentioning
confidence: 99%
“…A family of longer dolichols with [15][16][17][18][19][20][21][22][23] isoprene residues is present, in contrast with ubiquinone, which has only one major form in each individual species (nine isoprene residues in rat; ten in human).…”
Section: Structure Of Dolicholmentioning
confidence: 99%
“…Dolichol, a polyisoprenoid alcohol, was first isolated from pig liver, and is one of the largest lipids in eukaryotes and archaea (Burgos et al, 1963;Pennock et al, 1960). Named for the Greek word for long, dolichos, it can contain 14-24 isoprene units depending on the organism.…”
Section: Biosynthesis Of the Eukaryotic Dolichyl Lipid Carriersmentioning
confidence: 99%
“…Dolichol was isolated from pig liver by the method of Burgos et al [2]. Preparative thin-layer chromatography [3] was carried out developing first with chloroform and then eluting the dolichol band, which fluoresced when sprayed with Rhodamine G and gave a green-yellow colour when detected with anisaldehyde [3].…”
Section: Methodsmentioning
confidence: 99%
“…Polyisoprenols are also present in mammalian tissues [2,31, and their role as acceptors of hexoses from nucleotide sugars has been documented [4-lo]. Leloir and his associates [5, 7, 81 have found that a liver system readily transfers hexoses from sugar nucleotides to dolichol monophosphate.…”
Section: Introductionmentioning
confidence: 99%